2022
DOI: 10.48048/tis.2022.4583
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity Evaluation of Hydrogel Sheet Dressings Fabricated by Gamma Irradiation: Extract and Semi-Direct Contact Tests

Abstract: Cytotoxicity presents one of the required criteria in the biological evaluation of medical devices. In this study, the semi-direct contact test was used to evaluate the potential cytotoxicity of hydrogel wound dressings compared to the conventional extract test. Three types of hydrogel sheets were fabricated from poly(vinyl alcohol) (PVA) by gamma irradiation: Bare sheets, silver (Ag)-coated sheets, and Aloe vera (AV)-coated sheets. In the extract test, L929 cells were cultured in the extract derived from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(31 reference statements)
1
2
0
Order By: Relevance
“…In terms of the sensitivity of the different bacteria to the AgNPs, our findings also agreed with a previous report that the MIC of AgNPs against S. aureus was higher than the level required for E. coli [29]. Based on our previous study, the release of AgNPs from the hydrogels was qualitatively confirmed by UV-Vis spectrophotometry [30]. In the present study, the amount of released AgNPs at varied AgNO 3 loadings was quantitatively measured in the form of ionized Ag + by ICP-MS (Figure 6), which decreased proportionally from treatments A-E. For hydrogels A, B, and C incorporated with AgNPs at 1, 0.5, and 0.25 mg/cm 2 , respectively, the amount of released AgNPs increased sharply by approximately 26-43% between 2 and 24 h. After, the level of the released AgNPs remained relatively unchanged for up to 72 h. Interestingly, for treatments D and E, with a much lower initial AgNO 3 loading, the released AgNPs continued to rise linearly with the incubation time from 2 up to 72 h. Regarding the AgNP levels of 59 ± 5 ppm for hydrogel B and 32 ± 2 ppm for hydrogel C measured by ICP at 24 h, it can be derived from our experiment that at least ~30 and 60 ppm of AgNPs is required for effective antibacterial action against S. aureus and E. coli, respectively.…”
Section: Antibacterial Properties Of the Agnp-loaded Hydrogel Sheetssupporting
confidence: 92%
See 1 more Smart Citation
“…In terms of the sensitivity of the different bacteria to the AgNPs, our findings also agreed with a previous report that the MIC of AgNPs against S. aureus was higher than the level required for E. coli [29]. Based on our previous study, the release of AgNPs from the hydrogels was qualitatively confirmed by UV-Vis spectrophotometry [30]. In the present study, the amount of released AgNPs at varied AgNO 3 loadings was quantitatively measured in the form of ionized Ag + by ICP-MS (Figure 6), which decreased proportionally from treatments A-E. For hydrogels A, B, and C incorporated with AgNPs at 1, 0.5, and 0.25 mg/cm 2 , respectively, the amount of released AgNPs increased sharply by approximately 26-43% between 2 and 24 h. After, the level of the released AgNPs remained relatively unchanged for up to 72 h. Interestingly, for treatments D and E, with a much lower initial AgNO 3 loading, the released AgNPs continued to rise linearly with the incubation time from 2 up to 72 h. Regarding the AgNP levels of 59 ± 5 ppm for hydrogel B and 32 ± 2 ppm for hydrogel C measured by ICP at 24 h, it can be derived from our experiment that at least ~30 and 60 ppm of AgNPs is required for effective antibacterial action against S. aureus and E. coli, respectively.…”
Section: Antibacterial Properties Of the Agnp-loaded Hydrogel Sheetssupporting
confidence: 92%
“…In the present study, the amount of released AgNPs at varied AgNO 3 loadings was quantitatively measured in the form of ionized Ag + by ICP-MS (Figure 6), which decreased proportionally from treatments A-E. For hydrogels A, B, and C incorporated with AgNPs at 1, 0.5, and 0.25 mg/cm 2 , respectively, the amount of released AgNPs increased sharply by approximately 26-43% between 2 and 24 h. After, the level of the released AgNPs remained relatively unchanged for up to 72 h. Interestingly, for treatments D and E, with a much lower initial AgNO 3 loading, the released AgNPs continued to rise linearly with the incubation time from 2 up to 72 h. Regarding the AgNP levels of 59 ± 5 ppm for hydrogel B and 32 ± 2 ppm for hydrogel C measured by ICP at 24 h, it can be derived from our experiment that at least ~30 and 60 ppm of AgNPs is required for effective antibacterial action against S. aureus and E. coli, respectively. Based on our previous study, the release of AgNPs from the hydrogels was qualitatively confirmed by UV-Vis spectrophotometry [30]. In the present study, the amount of released AgNPs at varied AgNO3 loadings was quantitatively measured in the form of ionized Ag + by ICP-MS (Figure 6), which decreased proportionally from treatments A-E. For hydrogels A, B, and C incorporated with AgNPs at 1, 0.5, and 0.25 mg/cm 2 , respectively, the amount of released AgNPs increased sharply by approximately 26-43% between 2 and 24 h. After, the level of the released AgNPs remained relatively unchanged for up to 72 h. Interestingly, for treatments D and E, with a much lower initial AgNO3 loading, the released AgNPs continued to rise linearly with the incubation time from 2 up to 72 h. Regarding the AgNP levels of 59 ± 5 ppm for hydrogel B and 32 ± 2 ppm for hydrogel C measured by ICP at 24 h, it can be derived from our experiment that at least ~30 and 60 ppm of AgNPs is required for effective antibacterial action against S. aureus and E. coli, respectively.…”
Section: Antibacterial Properties Of the Agnp-loaded Hydrogel Sheetsmentioning
confidence: 87%
“…In this method, the tested materials are placed in direct touch with the cell culture in order to identify any potential toxicity even from weak toxic materials (17) . The direct contact method is highly sensitive and able to detect weak cytotoxicity.…”
Section: Test By Direct Contactmentioning
confidence: 99%